Prinsip Hidup Menang Atas Dosa Menurut Rasul Paulus Dalam Roma 6 - Lewy, Lewy; Tanhidy, Jamin (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2019)
This article explain the principles how human being can overcoming sin according to the teaching of Apostle Paul in Romans chapter six. Because mankid have sinned  make their life far from God, but God in Christ came into the world and wiped out all human’s  sins through the redemption of Jesus Christ, all these truth revealed because of God's grace and His goodness. In Romans chapter six the Apostle Paul explains how the justified manwho has been sanctified by the Holy Spirit regarding the power against sin  by practicing some basic truth such as lived not to sin, not allowing sin control the body, walk in newness of life and  live in  communion with Christ. Tulisan ini membahas prinsip hidup menang dari dosa berdasarkan ajaran Paulus dalam Roma Pasal 6.  Akibat dosa yang telah membelenggu umat manusia membuat kehidupan manusia jauh dari Allah, tetapi Allah di dalam Kristus datang menghapus semua dosa semua orang melalui penebusan Kristus, semua kebenaran ini dinyatakan karena kebaikan dan anugerah Allah. Dalam Roma pasal 6 Rasul Paulus menjelaskan bagaimana manusia yang telah dibenarkan itu selanjutnya dikuduskan oleh Roh Kudus dikaruniakan kuasa untuk menang atas dosa dengan mempraktekkan prinsip tidak hidup dalam dosa, tidak membiarkan dosa menguasai tubuh, hidup sebagai manusia baru, dan hidup dalam persekutuan dengan Kristus.